2021
DOI: 10.21203/rs.3.rs-610941/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Equine Grass Sickness (A Multiple Systems Neuropathy) is Associated with Alterations in the Gastrointestinal Mycobiome

Abstract: Background: Equine grass sickness (EGS) is a multiple systems neuropathy of grazing horses of unknown aetiology. An apparently identical disease occurs in cats, dogs, rabbits, hares, sheep, alpacas and llamas. Many of the risk factors for EGS are consistent with it being a pasture mycotoxicosis. To identify potential causal fungi, the gastrointestinal mycobiota of EGS horses were evaluated using targeted amplicon sequencing, and compared with those of two control groups. Samples were collected post mortem from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The primary DNA barcode for eukaryotes like fungi is the ITS1 region between the 18S rRNA and 5.8S rRNA genes [59]. The authors chose to use ITS1 primers like those used in McGorum et al [60], who collected postmortem samples from the gastrointestinal tract of 54 horses with equine grass sickness and faecal samples from control horses. Results seen in McGorum et al [60] are somewhat comparable to the current study, finding Acremonium, Preussia and Naganishia fungal species to be among the most dominant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary DNA barcode for eukaryotes like fungi is the ITS1 region between the 18S rRNA and 5.8S rRNA genes [59]. The authors chose to use ITS1 primers like those used in McGorum et al [60], who collected postmortem samples from the gastrointestinal tract of 54 horses with equine grass sickness and faecal samples from control horses. Results seen in McGorum et al [60] are somewhat comparable to the current study, finding Acremonium, Preussia and Naganishia fungal species to be among the most dominant.…”
Section: Discussionmentioning
confidence: 99%
“…The authors chose to use ITS1 primers like those used in McGorum et al [60], who collected postmortem samples from the gastrointestinal tract of 54 horses with equine grass sickness and faecal samples from control horses. Results seen in McGorum et al [60] are somewhat comparable to the current study, finding Acremonium, Preussia and Naganishia fungal species to be among the most dominant. However, it is unknown why Neocallimastigomycota species or other anaerobic fungal phyla known to colonise the alimentary tract of mammalian herbivores and hindgut fermenters were not detected in faecal samples analysed in the current study [24,52,[61][62][63][64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of soil‐based mycotoxin involvement in the aetiology of EGS has also been investigated using molecular techniques to type the gastrointestinal mycobiota. This showed that some key phylotypes had high prevalence and abundance in EGS cases compared to healthy control cases (McGorum and others 2021). The theory of certain fungi producing neurotoxins as a causal agent would also be consistent with the seasonality of EGS cases, as well as pasture and climate spatiality.…”
Section: Identifying the Causementioning
confidence: 92%